2011
DOI: 10.1186/1479-5868-8-119
|View full text |Cite
|
Sign up to set email alerts
|

Age, puberty, body dissatisfaction, and physical activity decline in adolescents. Results of the German Health Interview and Examination Survey (KiGGS)

Abstract: BackgroundPhysical activity (PA) shows a marked decline during adolescence. Some studies have pointed to pubertal status or timing as possible PA determinants in this age group. Furthermore, it was supposed that the impact of pubertal changes on PA might be mediated by psychological variables like body dissatisfaction (BDS).MethodsThe 11- to 17-year-old subsample of the German Health Interview and Examination Survey (KiGGS) was used (n = 6 813; 51.3% male, response rate = 66.6%). Through sex-specific sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 58 publications
(99 reference statements)
9
66
0
14
Order By: Relevance
“…Thus, the association between body image dissatisfaction and low physical activity levels is well established in both sexes (31) ; however, no study on the association between physical fitness and body image was found for any age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the association between body image dissatisfaction and low physical activity levels is well established in both sexes (31) ; however, no study on the association between physical fitness and body image was found for any age.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas body dissatisfaction occurs for both sexes, it is more prevalent (and salient) for girls than boys (Finne et al, 2011;Sujoldzić & De Lucia, 2007). The combination of pubertal changes, increased self-introspection, and more interest in romantic relationships can contribute to adolescents being critical of their physical appearance and dissatisfied with their body size and shape (Ferreiro, et al 2012).…”
Section: Body Satisfactionmentioning
confidence: 99%
“…Given increases in obesity and depression among adolescents, combined with declines in fitness levels (Dyrstad et al, 2012;Finne et al, 2011;Grunbaum et al, 2004;Kimm et al, 2000;Olds et al, 2006;Tomkinson et al, 2003;Tomkinson et al, 2007), there is a need to understand how these three conditions interrelate and develop from childhood through adolescence. Moreover, we did not examine personality factors, such as neuroticism, or underlying biomarkers (e.g., changes in neurotransmitters) related to depression which may provide further explanations or impact the results.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations